Mercury toxicity on differential distribution of dehydrogenases in various regions of the brain in L. rohita (Ham.) - Shaffi, S A (Indian Journal of Fisheries, 2011)
The sublethal effect of mercury on differential distribution of oxidative enzymes (glucose - 6- phosphate dehydrogenase, NAD-isocitrate dehydrogenase, NADP-isocitrate dehydrogenase) in different brain regions (cerebrum, diencephalon, cerebellum, medulla oblongata) under acute, chronic and detoxication studies were investigated in L. rohita. The highest rise in the enzymes was in cerebrum (0 to 8 hrs) and the lowest in cerebellum (8 to 16 hrs) during acute studies. During chronic studies, maximum rise was in the oxidative enzymes in cerebrum (0 to 15 days) and minimum in cerebellum (evenly). In detoxication studies the fast fall in the oxidative enzymes was in cerebellum (0 to 15 days) and slow fall in cerebrum (30 to 45 days).